The Urgency Of Regulation Of Non Conviction Based Asset Forfeiture In Corruption Criminal Acts In Indonesia - Aldino, Masagus Rizki; Susanti, Emilia (JURNAL HUKUM SEHASEN, 2025)
Regulations for confiscation of assets without punishment in Indonesia are currently not clearly regulated in statutory regulations. Currently, Indonesia only regulates asset confiscation through the criminal process. Confiscation of assets without punishment or non-conviction based asset forfeiture/NCB is the concept of returning state losses without first imposing a crime on the perpetrator. This concept was developed in several countries that adhere to a common law legal system such as the United States. This concept aims to ensure that confiscation of assets resulting from criminal acts, especially corruption crimes, is implemented optimally and does not cause problems in the future. Researchers are interested in studying and examining the urgency of implementing the concept of confiscation of assets without punishment which is regulated in the legal system in Indonesia with appropriate reviews and provisions in the United Nations Convention Against Corruption. In article 54 paragraph (1) UNCAC has regulated that all countries must consider taking actions deemed necessary so that confiscation of assets resulting from corruption is possible without criminal proceedings in cases where the perpetrator cannot be prosecuted by reason of death, flight or not being found. The approach used in this research is normative juridical, secondary data is the main data